Application of dynamic speckle methods to study thermal denaturation of the albumin - Li, Xinzhong; Tai, Yuping; Nie, Zhaogang; Chen, Qingdong; Li, Liben (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The process of the thermal denaturation of albumin was studied using dynamic speckle methods, which included the time history of speckle patterns (THSP), the THSP based on wavelet entropy (WE), speckle size measurement and the speckle pattern mean contrast techniques. In experiments, the dynamic speckle pattern sequences produced from the albumin colloid during heat denaturation were obtained using CCD camera. And then, using these dynamic speckle methods, the change of the movement properties of protein particles was analyzed during the heating process. All results show that the protein particles become bigger, their mean free path becomes shorter and the velocity of the Brownian movement becomes slower during the heating process. The experiments prove that dynamic speckle methods are useful tools to investigate the particles motion in solution.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 579-591
Keywords: optyka; dynamic speckle; albumin; thermal denaturation; protein particles